Impact of industrialization and renewable energy on carbon dioxide emission in 9 ASEAN countries - Claire, Barbara; Widyawati, Diah (Economic Journal of Emerging Markets, 2023)
Purpose ― This research investigates the relationship between ASEAN's industrialization, renewable energy, and CO2 emissions. The primary objectives are to assess the existence of the Environmental Kuznets Curve (EKC) in ASEAN and to explore the potential mediating effect of renewable energy in the relationship between industrialization and CO2 emissions.Methods ― The study utilizes the PMG-ARDL estimation method in nine ASEAN countries from 1990 to 2019, providing short- and long-term analyses of the variables involved.Findings ― The finding reveals the presence of the EKC in ASEAN in the short term for most member states. It also finds that renewable energy mediates the relationship between industrial value-added and CO2 emissions, with renewable energy adoption altering the turning point of per capita CO2 emissions during industrialization in several ASEAN nations.Implication ― The findings suggest that transitioning to renewable energy can help mitigate the environmental impact of ASEAN’s industrial development. Thus, member states committed to energy targets should prioritize deploying renewable energy in their industrial sectors to achieve environmental benefits.Originality ― This research contributes to the existing literature by specifically examining the interplay between industrialization, renewable energy, and CO2 emissions in ASEAN. The use of the PMG-ARDL estimation method and the focus on the mediating role of renewable energy add originality to the study.